1997
DOI: 10.1177/016235329702000406
|View full text |Cite
|
Sign up to set email alerts
|

An Action Research Study of the Effectiveness of Problem-Based Learning in Promoting the Acquisition and Retention of Knowledge

Abstract: This action research study compares the efficacies of problem-based learning (PBL), traditional lecture, and a combination of PBL and traditional lecture to promote understanding and retention of the principle content of an elective science course, biochemistry, taught at a school for talented students. The study utilizes a pre- and post-course self-evaluation of student understanding, a measure of depth of understanding, and a questionnaire designed to determine student satisfaction. Lecture tended to widen t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 8 publications
1
54
1
3
Order By: Relevance
“…Extant research demonstrated that while lecture results in better achieving mastery of content, alternative teaching methods, including problem-based learning and simulations, create deeper understanding and retention of material (Bligh, 2000;Bok, 2006;Dods, 1997;Polich & Goodell, 2007a;Polich & Goodell, 2007b;Sutherland & Bonwell, 1996). The overwhelming consensus in the literature seems to be that lecture "is not highly effective to help students accomplish [complex] student learning outcomes" and that "in studies measuring information retention after a course, transfer of knowledge in new situations, problem solving, thinking, attitude change and motivation, active learning was always more effective than pure lecture as a teaching technique" (Center for Instructional Technology, n.d.; Hake, 1998).…”
Section: Relevant Pedagogical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Extant research demonstrated that while lecture results in better achieving mastery of content, alternative teaching methods, including problem-based learning and simulations, create deeper understanding and retention of material (Bligh, 2000;Bok, 2006;Dods, 1997;Polich & Goodell, 2007a;Polich & Goodell, 2007b;Sutherland & Bonwell, 1996). The overwhelming consensus in the literature seems to be that lecture "is not highly effective to help students accomplish [complex] student learning outcomes" and that "in studies measuring information retention after a course, transfer of knowledge in new situations, problem solving, thinking, attitude change and motivation, active learning was always more effective than pure lecture as a teaching technique" (Center for Instructional Technology, n.d.; Hake, 1998).…”
Section: Relevant Pedagogical Literaturementioning
confidence: 99%
“…Video diaries, for instance, were found to be successful in fostering transformative, integrative, and irreversible knowledge of sustainability among participants in a British travel course to rural Uganda (Roberts, 2011). The teaching Published by Scholarship@Western, 2015 modality that the instructor employs to introduce students to sustainability involves role-playing simulation, one of the most popular offerings in the active learning repertoire.Extant research demonstrated that while lecture results in better achieving mastery of content, alternative teaching methods, including problem-based learning and simulations, create deeper understanding and retention of material (Bligh, 2000;Bok, 2006;Dods, 1997;Polich & Goodell, 2007a;Polich & Goodell, 2007b;Sutherland & Bonwell, 1996). The overwhelming consensus in the literature seems to be that lecture "is not highly effective to help students accomplish [complex] student learning outcomes" and that "in studies measuring information retention after a course, transfer of knowledge in new situations, problem solving, thinking, attitude change and motivation, active learning was always more effective than pure lecture as a teaching technique" (Center for Instructional Technology, n.d.; Hake, 1998).…”
mentioning
confidence: 99%
“…Of the 33 studies, fi ve assessed the impact of PBL on deep content learning (see Table 1) using the following measure types: multiple choice questions (Aaron et al, 1998), self-report surveys about approaches to studying (Newble & Clarke, 1986), and depth of understanding of terms (Dods, 1997), essay questions (Antepohl & Herzig, 1999;Finch, 1999), list of terms to defi ne (Dods), and presentation of a case after which the next steps needed to be suggested (Aaron et al).…”
Section: Deep Content Learningmentioning
confidence: 99%
“…Estudos como os de Dods (1997) e Newble e Clarke (1986) mostraram que a PBL é eficaz na promoção de certos tipos de aprendizagem. Como foi observado pelos autores, os participantes das pesquisas ganharam maior aprofundamento na compreensão do conteúdo do que os métodos tradicionais de ensino, que se concentram na amplitude do conhecimento.…”
Section: Pbl -Problem-based Learning: Aprendizagem Baseada Em Problemaunclassified